The gender line : men, women, and the law - Levit, Nancy (Critical America., 1998)
"With its focus particularly on men, The Gender Line offers an insightful overview of the construction of gender and the damaging effects of its stereotypes. Levit analyzes the ways in which law legitimizes the social segregation of the sexes through legal decisions regarding custody, employment, education, sexual harassment, and criminal law. In so doing, she illustrates the ways in which men's and women's oppressions are intertwined and how law molds the very definition of masculinity."--Jacket